Engineering CpG‐ASO‐Pt‐Loaded Macrophages (CAP@M) for Synergistic Chemo‐/Gene‐/Immuno‐Therapy. Issue 15 (19th June 2022) - Wang, Yuqi; Zhang, Lingpu; Liu, Yan; Tang, Linlin; He, Juan; Sun, Xiaqing; Younis, Muhsin H.; Cui, Daxiang; Xiao, Haihua; Gao, Dong; Kong, Xiang‐Yang; Cai, Weibo; et al.
Abstract: Adoptive cell therapy by natural cells for drug delivery has achieved encouraging progress in cancer treatment over small‐molecule drugs. Macrophages have a great potential in antitumor drug delivery due to their innate capability of sensing chemotactic cues and homing toward tumors. However, major challenge in current macrophage‐based cell therapy is loading macrophages with adequate amounts of therapeutic, while allowing them to play a role in immunity without compromising cell functions. Herein, a potent strategy to construct a macrophage‐mediated drug delivery platform loaded with a nanosphere (CpG‐ASO‐Pt) (CAP) composed of functional nucleic acid therapeutic (CpG‐ASO) and chemotherapeutic drug cisplatin (Pt) is demonstrated. These CAP nanosphere loaded macrophages (CAP@M) are employed not only as carriers to deliver this nanosphere toward the tumor sites, but also simultaneously to guide the differentiation and maintain immunostimulatory effects. Both in vitro and in vivo experiments indicate that CAP@M is a promising nanomedicine by macrophage‐mediated nanospheres delivery and synergistically immunostimulatory activities. Taken together, this study provides a new strategy to construct a macrophage‐based drug delivery system for synergistic chemo‐/gene‐/immuno‐therapy. Abstract : A multifunctional self‐assembled DNA nanosphere through adoptive macrophages delivery is developed for cancer treatment. The DNA nanosphere loaded macrophages not only are employed as carriers to deliver nanosphere toward tumor sites, but also simultaneously play a role in immune regulation. This study offers a promising strategy to construct a macrophage‐based drug delivery nanoplatform for synergistic therapy.